Characterization of Visual Acuity and Contrast Sensitivity using Head-Mounted Displays in a Virtual Environment: A Pilot Study. (November 2019) - Sproule, David; Jacinto, Rosemarie Figueroa; Rundell, Steve; Williams, Jacob; Perlmutter, Sam; Arndt, Steve
Virtual reality (VR) and personal head-mounted displays (HMDs) can be a viable tool for the presentation of scientifically accurate and valid demonstrative data in the courtroom. However, the capabilities and limitations of the technology need to be fully characterized. The current pilot study evaluated visual acuity and contrast sensitivity using two commercially available HMDs (Oculus Rift and HTC Vive Pro). Preliminary findings indicated that visual acuity and contrast sensitivity experienced in VR may be less than what is experienced in real-world scenarios. The current pilot study provides a quantitative approach for characterizing the limitations of VR with respect to visual acuity and contrast sensitivity, and provides recommendations for the appropriate use of this technology when performing forensic investigations and developing visualization tools.